2018
DOI: 10.29252/ijrm.16.5.299
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte-colony stimulating factor may improve pregnancy outcome in patients with history of unexplained recurrent implantation failure: An RCT

Abstract: Background:Family of colony-stimulating factors (CSF) have an essential role on early cross talk between embryo and uterine endometrium.Objective:The aim of this study was to evaluate the effects of the single dose of Granulocyte-CSF (G-CSF) injection on clinical outcome of assisted reproductive technology cycle in patients with repeated implantation failures.Materials and Methods:This randomized control trial study was performed on 52 infertile women who referred to the clinic with the history of more than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…This cytokine promotes endometrial immunomodulation and optimizes the interaction between the embryo and the endometrium. Studies have shown that its use is associated with higher pregnancy rates and lower miscarriage rates (Lédée et al ., 2013; Rahmati et al ., 2015; Arefi et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This cytokine promotes endometrial immunomodulation and optimizes the interaction between the embryo and the endometrium. Studies have shown that its use is associated with higher pregnancy rates and lower miscarriage rates (Lédée et al ., 2013; Rahmati et al ., 2015; Arefi et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Implantation loss contributes greatly to the pregnancy loss for humans and mammalian animals [9,34]. To dissect the underlying mechanism of proliferative endometrial defects in implantation loss, a proteomic analysis of endometrium 12 Oxidative Medicine and Cellular Longevity from NRP and LRP sows was conducted in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Different populations selected (infertile, RIF, cases with thin endometrium), different ways of administration (intrauterine, subcutaneously), different concentrations offered and different study endpoints made it difficult to extract a solid conclusion. So far 10 randomized controlled trials have been published ( Barad et al, 2014 ; Aleyasin et al, 2016 ; Davari-Tanha et al, 2016 ; Eftekhar et al,2016a,b ; Sarvi et al, 2017 ; Arefi et al, 2018 ; Bakirarar et al, 2018 ; Huang et al, 2020a ; Kalem et al, 2020 ), with conflicting results, followed by meta-analyses in a timely manner (presented in Table 5 ). The six meta-analyses published present rather supportive results ( Zhao et al, 2016 ; Kamath et al, 2017 ; Li et al, 2017a ; Hou et al, 2018 ; Jiang et al, 2020 ; Kamath et al, 2020 ).…”
Section: Approaches To Improve Endometrial Receptivity In Unexplainedmentioning
confidence: 99%